Digital Green Waqf, Institutional Governance, and Economic Resilience in Islamic Financial Institutions: A Neo-Integrated Islamic Market Justice Approach - Febri Delmi Yetti; Anton Bawono; Abdul Aziz; Wartoyo; Sri Rokhlina Sari (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
The rapid digital transformation in the financial sector has stimulated new innovations in Islamic social finance, particularly in the governance of waqf institutions. One emerging concept is Digital Green Waqf, which integrates digital technology into waqf management while directing investments toward sustainability-oriented projects. However, empirical evidence explaining how digital waqf initiatives influence institutional governance and sustainability outcomes within Islamic financial institutions remains limited. This study aims to examine the role of Digital Green Waqf in strengthening governance quality, sustainability investment, and economic resilience in Islamic financial institutions in Indonesia using the theoretical framework of Neo-Integrated Islamic Market Justice (Neo-IIMJ). The research adopts a mixed-method approach combining quantitative panel data analysis with qualitative institutional interpretation. Secondary data covering the period 2015–2024 were obtained from the Indonesian Waqf Board (BWI), BAZNAS statistics, Bank Indonesia reports, and World Bank development indicators. Panel regression analysis is used to examine the relationship between digital waqf development, governance quality, sustainability outcomes, and economic resilience. The findings indicate that Digital Green Waqf significantly improves governance transparency and promotes sustainability-oriented waqf investment, which subsequently strengthens economic resilience. These results demonstrate the growing institutional role of digital waqf in enhancing the governance capacity of Islamic financial institutions. This study contributes theoretically by integrating Digital Green Waqf within the Neo-Integrated Islamic Market Justice framework as an institutional model linking digital innovation, governance accountability, and sustainability in Islamic financial systems, while also providing policy insights for strengthening waqf governance, accelerating digital transformation in Islamic financial institutions, and supporting sustainable development agendas aligned with the Sustainable Development Goals (SDGs).